Special force training of qualified cross-country skiers of 18-20 years old in the preparatory period - Serhii Kotliar; Oleksandr Toporkov; Tetiana Sidorova (Kharkiv State Academy of Physical Culture, 2021)
Purpose: improving special strength training of qualified cross-country skiers of 18-20years old in the preparatory period of annual macrocycle. Material and methods: the study was attended by athletes aged 18-20 years,who had training at the level of the first sports category, Candidate Master of Sports, experience of skiing 8-10 years. The control group (n = 10) conducted a training process according to the children's and youth sports school program, experimental (n = 10) with the useof special exercises taking into account the style of movement and muscles involved. At the end of the stages of training with the helpof special tests on inline skates and a ski simulator, a control test of the development of special strength qualities was conducted, andafter the study, athletes took part in competitions with inline skates in different styles. Results: as a result of the use of special strengthtraining in the mode (special physical training and general physical training - 80/20%), there was an improvement in the results of test indicators of special training by 3,33-18,09% and indicators obtained during the competition: the results in the sprint race in the classic style improved by 23,63% (t = 5,67; p <0,01); sprint in skating style by 24,86% (t = 8,13; p <0,01); in the 10 km classic race 9,77% (t = 4,01; p <0,01); in the 10 km skating style race 6,82% (t = 2,43; p <0,05). Conclusions: continuous strength training by skiers-racers inthe preparatory period made it possible to ensure control and management of the training process, despite the conditions of quarantine. Using of the proposed method, promoted more rational and productive training process of skiers-racers. The ratio of special physicaltraining and general physical training in the preparatory period has a crucial role in the training process of qualified cross-country skiers-racers of 18-20 years old.